How Governance Regimes Shape the Implementation of Water Reuse Schemes - Frijns, Jos; Smith, Heather M.; Brouwer, Stijn; Garnett, Kenisha; Elelman, Richard; Jeffrey, Paul (MDPI, 2016)
The governance dimensions of water reuse scheme development and operation, such as policies and regulatory frameworks, and public involvement and stakeholder collaboration, can serve to both facilitate and constrain wider adoption of water reuse practices. This paper explores the significance and underlying structure of the key governance challenges facing the water reuse sector in Europe. It presents empirical evidence from interviews and focus group sessions conducted at four water reuse schemes: an indirect potable reuse scheme at Torreele (Belgium), the urban reuse of treated municipal wastewater at the London Olympic Park (United Kingdom) and at Sabadell (Spain), and the reuse of agro-industrial effluent for irrigation at Capitanata (Italy). The findings underscore the importance of clarity in policy arrangements around water reuse, as well as of the financial competitiveness of reuse projects compared to alternative water supply options. Operators of water reuse schemes expressed a preference for water quality standards, which focus on appropriateness for use rather than over-emphasise the waters’ origin so that unnecessary treatment and costs can be avoided. Positive public support was widely acknowledged as an important factor in the success or failure of water reuse schemes. We conclude that constructive institutional relationships underpin many of the challenges faced by reuse scheme operators and that greater emphasis should be given to building confidence and gaining trust in water service providers through early identification of how governance regimes shape the viability of new schemes
Keywords: governance; policy; public participation; stakeholder collaboration; water reuse